Consumer Ethical Decision Making: Linking Moral Intensity, Self-Consciousness and Neutralization Techniques - Syed Afzal Moshadi Shah; Shehla Amjad (Australasian Accounting, Business and Finance Journal, 2017)
The purpose of the study is to examine the effect of moral intensity on self-conscious emotions and neutralization techniques in the context of ethical decision making among consumers. A sample of 388 shopping mall retail consumers was recruited through self-administered survey technique. Descriptive statistics, exploratory factor analysis, correlation was carried out in SPSS whereas the measurement model and structural relationships were estimated using AMOS. Results indicate that moral intensity positively influences consumer’s self-consciousness, neutralization techniques and behavioural intention. Self-consciousness negatively influence consumer’s defence mechanism i.e. neutralization techniques. Neither self-consciousness nor neutralization techniques is found to have an impact on consumers’ behavioural intention. Only self-consciousness is found to complementary mediate the relationship of moral intensity and neutralization. The limitations associated with field survey and cross-sectional research design are inevitable. The study offers some relevant practical implications for government, marketing professionals and academia. The study is among the pioneer studies that theoretically links and empirically examines Issue Contingent Model, theory of neutralization and self-consciousness. The study develops and tested an Urdu language version of the questionnaire for retail consumers.
Keywords: Moral Intensity; Self-consciousness; Neutralization Techniques; Behavioural Intention; Consumer Ethics; Decision Making